Sparing ultrasound in emergency department patients with suspected deep vein thrombosis by using clinical scores and d‐dimer testing. Issue 4 (15th December 2015) - Gaitini, Diana; Khoury, Rasha; Israelit, Shlomo; Beck‐Razi, Nira
ABSTRACT: Purpose: To evaluate compliance with a management strategy for use in emergency department (ED) patients with suspected deep vein thrombosis (DVT) based on Wells score (WS), d ‐dimer concentrations, and sonographic (US) examinations. Methods: Retrospective and prospective data on risk factors, physical examination findings, d ‐dimer concentrations, and US results were collected and reviewed. The prevalence of DVT for each WS category andd ‐dimer level was calculated. Results: In the retrospective part of the study, 475 consecutive patients were included. Patients' risk for DVT was scored as high (n = 129 [27.2%]), moderate (n = 95 [20%]), or low (n = 251 [52.8%]).d ‐Dimer test results were available for 34 (7.2%) of the patients. DVT was diagnosed in 105 (22.1%) patients: 99 (76.7%) at high, 4 (4.2%) at moderate, and 2 (0.8%) at low risk. The meand‐ dimer concentration was 3, 071.7 ng/ml in patients with DVT. In the prospective part of the study, 50 patients were enrolled. Their risk levels for DVT were scored as high (n = 23 [46%]), moderate (n = 7 [14%]), and low (n = 20 [40%]).d‐ Dimer testing was performed in all patients. The meand ‐dimer concentration was 2, 966.9 ng/ml in patients with DVT. DVT was diagnosed in 13 (26%) of these 50 patients: 12 (52.2%) at high and 1 (14.3%) at moderate risk for DVT. No patients in the low‐risk group and with normald ‐dimer concentrations had DVT. Conclusions: We identified significant correlation between WS, d ‐dimer concentration, and diagnosis of DVT on US examination. DVT can be excluded with certainty in patients admitted to the ED with a low‐risk score for DVT and a negatived ‐dimer concentration, thus avoiding the need for performing US examinations. A low level of compliance with this management strategy was found in our ED. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound 44 :231–239, 2016